Impact of respiratory care training and family support using telemedicine on tracheostomized children admitted with respiratory infection after discharge - Prakarn Tovichien; Nuntiya Khaowsibsam; Bararee Choursamran; Pawinee Charoensittisup; Apinya Palamit; Kanokporn Udomittipong (BMC, 2023)
Abstract Objective Children with tracheostomies usually require a long hospital stay, high healthcare costs and caregiver burden. With the help of telemedicine, this study attempted to determine how home respiratory care training and family support affected admission days, admission costs, ICU admission rates, and caregivers' confidence. Methods We enrolled children with tracheostomies who were admitted between 2020 and 2022 with respiratory infections. Before discharge, we evaluated the knowledge and skills of the caregivers and gave them practice in home respiratory care while providing them with structured feedback using a checklist, a peer-to-peer mentor assignment, a virtual home visit, teleeducation, and teleconsultation via a mobile application. We compared the admission days, admission costs, and ICU admission rates one year following the program with the historical control one year earlier. Results Forty-eight children with tracheostomies were enrolled. Thirteen percent of those had a 1-year readmission. The median [IQR] number of admission days decreased from 55 [15-140] to 6 [4-17] days (p value < 0.001). The median [IQR] admission costs decreased from 300,759 [97,032 - 1,132,323] to 33,367 [17,898-164,951] baht (p value < 0.001). The ICU admission rates decreased from 43.8% to 2.1% (p value < 0.001). Immediately after the program, caregivers' confidence increased from 47.9% to 85.5% (p value < 0.001). Conclusions This respiratory care training and telehealth program decreased admission days, admission costs, and ICU admission rates for children with tracheostomies admitted with respiratory infections. The confidence of caregivers was also increased immediately after the program.